Factors Affecting The Consumers’ʹ Purchase Decision Safe Food: Case Study in Vietnam - Đào Quyết Thắng; Đoàn Việt Dũng; Nguyễn Thị Thùy Dung; Nguyễn Thị Thùy Giang (My University, 2019)
Factors Affecting The Consumers’ʹ Purchase Decision Safe Food: Case Study in Vietnam
Keywords: Consumer decision; Safe food; Vietnam